Delivering women-centred maternity care with limited resources: Grenada. - LAUKARAN, Virginia Hight (1994)
Identifies the operational features and the most essential factors that contribute to safe pregnancy for women in the system which uses limited technology. Indicates some obstacles to applying this system to other countries.